Semantic Derogation in K-pop Fandom Discourse: A Study of Gendered Nicknaming Practices - Kadir, Nur Rizka (Universitas Gadjah Mada, 2025)
Semantic derogation as a direct example of sexist language can be seen in many contexts. This study focuses on the phenomenon of semantic derogation in the nicknaming practices within K-pop fandom discourse, particularly on how female and male idols are linguistically targeted based on gender. It aims to analyze derogatory nicknames collected from posts on X, where fan wars frequently occur. The data is categorized by gender and examined through critical discourse analysis at the level of words (Mills, 2008). Findings reveal that female idols are more frequently subjected to sexually charged and demeaning terms (e.g., “Seoul Cycle”, “Jenwhore”), while male idols are insulted based on their appearance or perceived irrelevance (e.g., “Pigmin”, “Fadhyung”). This indicates a gendered double standard, where women are disproportionately sexualized and criticized for their success, whereas men are ridiculed for superficial traits. These practices reflect deep-rooted sexist ideologies and internalized misogyny within digital fan communities. Furthermore, it highlights how fandom language reinforces traditional gender roles and calls for further research into the socio-cultural roots of such bias.